Transmucosal Absorption Enhancers in the Drug Delivery Field - Maher, Sam (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Development of strategies to assist the movement of poorly permeable molecules across biological barriers has long been the goal of drug delivery science. In the last three decades, there has been an exponential increase in advanced drug delivery systems that aim to address this issue. However, most proprietary delivery technologies that have progressed to clinical development are based on permeation enhancers (PEs) that have a history of safe use in man. This Special Issue entitled "Transmucosal Absorption Enhancers in the Drug Delivery Field" aims to present the current state-of-the-art in the application of PEs to improve drug absorption. Emphasis is placed on identification of novel permeation enhancers, mechanisms of barrier alteration, physicochemical properties of PEs that contribute to optimal enhancement action, new delivery models to assess PEs, studies assessing safety of PEs, approaches to assist translation of PEs into effective oral, nasal, ocular and vaginal dosage forms and combining PEs with other delivery strategies.